Pengaruh Lama Fermentasi Menggunakan Aspergillus Niger dan Urea Terhadap Kadar Nutrisi Ampas Sagu (Metroxylon sp) - Daniel Daniel; Dedhi Yustendi; Fawwarahli Fawwarahli (Program Studi Peternakan Universitas Muslim Maros, 2023)
This research was carried out aiming to improve the nutritional quality of dregs sago (Metroxylon sp) through a fermentation process by utilizing the fungus Aspergillus niger. The treatment applied was the storage time of fermented dregs sago which consisted of 4 treatments and 3 replications thats is, P0 (without storage), P1 (7 days of storage), P2 (14 days of storage) and P3 (21 days of storage). The researched variables consisted of the percentage of crude fiber, crude protein and ekstract ether. Laboratory analysis data for each treatment obtained were tabulated in a table and analyzed using analysis of variance (ANOVA) with the F test at the 5% level and continued with Duncan's test if parameters were found to be significantly different between treatments (Steel and Torrie, 1990). The results showed that there was a significant difference (P<0.05) in the percentage of crude fiber and ekstract ether, while the percentage of crude protein content did not show a significant difference (P>0.05). 0 days, 7 days, 14 days and 21 days affected the percentage of crude fiber and ekstract ether but did not affect the percentage of crude protein of fermented dregs sago.